Pengembangan Alat Peraga Papan Penjumlahan pada Mata Pelajaran Matematika di Kelas 1 SDN 14 Pulau Punjung - Hader, Antik Estika; Darniyanti, Yulia; riani, sepia (Jurnal Ilmiah Dikdaya, 2024)
The low ability of students to carry out the addition process causes students to have difficultyunderstanding more complex material. Teachers must have the ability to innovate, be creative and be proactivein dealing with changes in trends and progress in using learning aids. Teachers must also produce learningprops that are creative, interesting and effective so that students do not feel bored with the monotonous learningprocess. The development objective that will be achieved in this research is to produce an Addition BoardTeaching Aid that is applied to Mathematics subjects in the valid, practical and effective categories. The modelused in this development is the ADDIE model. The method used in this research is Research and Development(R&D), which is a research method that aims to produce certain products and test the validity and effectivenessof these products in their application. The results of research on the validation sheet for the summation boardprops carried out by two validators produced an average score of 91% which was categorized as very valid.The results of research on the practicality sheet of the addition board teaching aids carried out by two teachersproduced an average score of 97% which was categorized as very practical. and the results of the trialassessment of the addition board teaching aids carried out by 18 students produced an average of 88.9% whichwas categorized as very effective